Economic leviathans - Johnston, Joseph (Statistical and Social Inquiry Society of Ireland, 1953)
Students of world economic affairs in the inter-war period were impressed by the extent to which the world scene was dominated by the economic policies (or impolicies) of two great economic leviathans : the U.S.A., and the United Kingdom as the centre of the sterling area. The smaller national economies, including our own, were, in relation to these, very much in the position of a dinghy in comparison with an Atlantic liner. We got the wash from their, sometimes, erratic movements, but there was very little we could do to save ourselves. If a smaller nation committed economic follies it was the chief sufferer itself, and the international economy was little affected by the actions of any one small national economy, though doubtless, in the aggregate, the actions of many small national economies were not without an important cumulative effect. In those days what really mattered on the world scale was the doings of the U.S.A. and the British Commonwealth of Nations. There was of course a third leviathan, away in Eastern Europe, but its economic relations with the rest of the world were compatible with the continued functioning of an international economy, or at all events they were not important enough to be able to upset it.
Read before the Society, 5 February 1953
Keywords: Global economic powers; International economic framework; 314.15